Dielectric and electrical properties of a mullite/glass composite from a kaolinite clay/mica-rich kaolin waste mixture - Grilo,J. P. F. (2019)
Abstract A mullite/glass composite has been prepared by reactive sintering of a kaolinite clay/mica-rich kaolin waste mixture with 25 wt% waste. Phase composition, microstructure, dielectric and electrical properties of the composite fired at 1400 °C were evaluated by X-ray diffraction, scanning electron microscopy and impedance spectroscopy (between 25 and 600 °C in air). The microstructural characterization showed the attainment of dense samples composed of acicular (orthorhombic) mullite (47.6 wt%), glassy phase (50.1 wt%), and residual quartz (2.3 wt%). Electrical conductivity (1.9x10-8 S/cm at 300 °C), dielectric constant (6.7 at 1 MHz, 25 °C) and dielectric loss (0.024 at 1 MHz, 25 °C) results gave evidence that the mullite/glass composite is a promising low-cost material for commercial use in electronics-related applications.